Response of Broiler Chicks Fed Increasing Levels of Copra Meal and Enzymes - Sundu, B.; Kumar, A.; Dingle, J. (International Journal of Poultry Science, 2005)
A study was performed to test the efficacy of three types of commercial enzymes, to determine how much copra meal can be used in chick diets and to investigate whether there is an interaction between type of enzyme and level of copra meal in the diets. Sixty four male Ross chicks were used in a two way factorial design experiment with four levels of copra meal (0, 10, 30 and 50 percent) and four enzyme treatments (no enzymes, `Hemicell`, `Allzyme SSF` and a combination of `Gamanase`, `Hemicell` and `Allzyme SSF`) with four replicates. All levels of inclusion of copra meal decreased weight gain, feed consumption, feed conversion efficiency, DM digestibility, nutrient digestibility, AME and jejunal content viscosity significantly. In general, the amount of decrease was proportional to the amount of copra meal in the diet. The inclusion of each enzyme significantly increased weight gain, feed conversion efficiency, DM digestibility, nutrient digestibility and decreased jejunal content viscosity. However, none of the enzyme treatments was able to completely overcome the growth depression of chicks caused by the inclusion of copra meal in the diet.